Analisis Kepuasan Pengguna Jaringan WiFi di Badan Pusat Statistika Lombok Tengah dengan Metode Servqual - Rial Husne; Sofiansyah Fadli (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
Reliable internet connectivity is a crucial element in supporting work effectiveness at the Central Bureau of Statistics (BPS) in Central Lombok. However, users of the internal WiFi network have reported various issues, including inconsistent speed and weak signal stability. This study aims to analyze user satisfaction with the WiFi network services using the Servqual method, which assesses service quality based on five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. A quantitative approach was employed by distributing questionnaires to employees and staff who utilize the network. Data analysis was conducted by measuring the gap between users’ expectations and their perceptions of the service quality. The results show that most dimensions experienced a negative gap, particularly responsiveness (-0.47) and tangibles (-0.40), indicating inadequate response speed and suboptimal infrastructure conditions. Conversely, assurance (+0.40) and empathy (+0.27) showed positive gaps, reflecting users’ trust in the competence of IT staff and their perceived attentiveness. These findings highlight the need for technical evaluations, infrastructure improvements, and capacity building of human resources through regular training. This research contributes to the understanding of information technology service quality in the public sector and provides a foundation for strategic decision-making to enhance digital services. Moreover, the study encourages further research using mixed methods to gain a more comprehensive understanding of user satisfaction with WiFi services in government institutions.